A study on evaluation of pre and postoperative polysomnography for obstructive sleep apnea patients - Mohankumar, Venugopal; Rajasekar, M. K.; Veerasigamani, Narendrakumar; Sivaranjani, M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Obstructive sleep apnea is the most common form of sleep-disordered breathing. However, obstructive sleep apnea has been associated with much more insidious conditions, including hypertension, diabetes, heart disease, stroke, and daytime somnolence can lead to a dramatically increased risk of motor vehicle accidents. Methods: This study was conducted in our institution in 34 OSA patients. After thorough evaluation with PSG, dynamic MRI, DISE patients were treated with various surgeries depending on the level of obstruction. Commonly UPPP, ESP, zetaplasty, tonsillectomy, tongue base reduction were done either alone or in combination. Results: Pre and postoperative polysomnograhpy for obstructive sleep apnea was evaluated and statistically analyzed. Significant proportion of patients improved both subjectively and objectively as determined by reduction in AHI from 41.73±13.94 to 15.77±9.13, reduction in ESS from 16.41+3.09 to 5.14±3.41 and reduction in snoring. Conclusions: OSA can be easily treated with proper preoperative investigations, appropriate surgery, prevention of complications and continued lifestyle modifications.